2015
DOI: 10.1007/s00122-015-2457-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of a new powdery mildew resistance gene Pm2b in Chinese breeding line KM2939

Abstract: An allele of Pm2 for wheat powdery mildew resistance was identified in a putative Agropyron cristatum -derived line and used in wheat breeding programs. Powdery mildew (caused by Blumeria graminis f. sp. tritici, Bgt) is one of the most devastating wheat diseases worldwide. It is important to exploit varied sources of resistance from common wheat and its relatives in resistance breeding. KM2939, a Chinese breeding line, exhibits high resistance to powdery mildew at both the seedling and adult stages. It carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 56 publications
0
53
0
Order By: Relevance
“…Complete elimination of D-genome, altered 5A, 5B, 7A chromosomes and restructured 2A chromosome were detected in two hexaploid triticales N9116H and N9116M derived from the cross of common wheat cultivar and Austrian rye (Li et al 2015). In the present study, the deletion of 2DL chromosome arms and the altered 3A, 5A, 1B and 7B chromosome were detected in N9436B according to FISH karatypes of N9436B and its parent Shaanmai 611.…”
Section: Gish Analysis Of N9436bmentioning
confidence: 66%
“…Complete elimination of D-genome, altered 5A, 5B, 7A chromosomes and restructured 2A chromosome were detected in two hexaploid triticales N9116H and N9116M derived from the cross of common wheat cultivar and Austrian rye (Li et al 2015). In the present study, the deletion of 2DL chromosome arms and the altered 3A, 5A, 1B and 7B chromosome were detected in N9436B according to FISH karatypes of N9436B and its parent Shaanmai 611.…”
Section: Gish Analysis Of N9436bmentioning
confidence: 66%
“…Though the growing number of virulent strains has been reported in some parts of China, the gene occurs in high frequency in so many commercial cultivars as it is easily transferred from resistant to susceptible cultivars (Parks et al, 2008;Gao et al, 2012). Recently, Ma et al (2015) reported the presence of a new gene Pm2b in the cultivar KM2939, a Chinese breeding line, which exhibits high resistance to powdery mildew at both the seedling and adult stages. This gene was reported to carry a single dominant powdery mildew resistance allele of Pm2, designated as Pm2b and was mapped on chromosome 5DS, rendering the previous allelic designation Pm2 to be re-designated as Pm2a.…”
Section: Discussionmentioning
confidence: 99%
“…Several wheat cultivars are being developed and tested for resistance to wheat powdery mildew but their resistance is easily broken down due to continuous development of new and more virulent strains through genetic recombination (Piarulli et al, 2012;Hurni et al, 2014). Some of the developed cultivars carrying resistance genes to wheat powdery mildew lose their resistance even before they are made available for commercial production (Hao et al, 2015;Ma et al, 2015). It is, therefore, important that the development of resistant cultivars should target multiple resistances to disease isolates so that effective and lasting control can be attained.…”
Section: Introductionmentioning
confidence: 99%
“…Pm2a was the first Pm gene reported on chromosome arm 5DS with an original designation Pm2 and a re-designation Pm2a when the new allele Pm2b in the same locus was discovered (McIntosh and Baker 1970;Ma et al 2015). Gene Pm2a originated from the common wheat cultivar Ulka and was firstly located on chromosome 5D by monosomic analysis (McIntosh and Baker 1970).…”
Section: Discussionmentioning
confidence: 99%